Analisis Debit Air Alokasi dengan Debit Air Nyata di Bangunan Sadap pada Saluran Sekunder Daerah Irigasi Colo Timur - Muhammad Nafis Hafizhan Gandang; Agus Hari Wahyudi; Solichin Solichin (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The Colo Timur Irrigation Area covers 20,601.80 hectares with a main canal length of 64.15 km, passing through the regencies of Sukoharjo, Karanganyar, Sragen, and Ngawi. The water flow comes from the Wonogiri Serbaguna Dam, which is dammed by the Colo Weir in Sukoharjo. This irrigation area faces issues with uneven water distribution, and there is a need to check the water irrigation from the intake gates to conclude whether the operation and maintenance of the irrigation network are in accordance with standards. The study was conducted on the secondary canals of Geneng, Pulosari, and Krikilan, which are located upstream, midstream, and downstream, respectively. On the Geneng secondary canal, measurements were taken at B CT 5, Ge 1, and Ge 8 Ka. On the Pulosari secondary canal, measurements were taken at B CT 29, BPo 1, BPo 12 Ka, and BPo 12 Ki. On the Krikilan secondary canal, measurements were taken at B CT 40, Kk 1 Ka, and Kk 1 Ki. This study uses the Ratio of Water Distribution Implementation (RWDI) to determine the category of water distribution. The water discharge from the intake gates does not match the allocated water discharge. Factors causing the discrepancy in water discharge include (a) intake gates not being opened according to plan, (b) the presence of water pumps in the canals reducing irrigation water, and (c) the field operation system implementing water distribution rotations.